Emptiness and Nothingness in OMA's Libraries - Onur Şimşek (Megaron, 2019)
This paper aims to analyse the semantical paralells between the philosophical meaning of the terms nothingness and emptiness as they were used by the presocratic philosophers Parmenides and Democritos and the meaning of nothingness and emptiness in the theory and praxis of Rem Koolhaas. First the philosophical context where Parmenides and Democritus used the terms will be explained and the role, which these terms played in the prehistoric cosmovision will be underlined. Then these terms will be compared with some texts of Koolhaas, in which the very same terms play a major role. Further Koolhaas' concept will be analysed at two libraries, namely the Seattle Central Library and the Très Grande Bibliothèque in Paris.